(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2020)
Three fractions obtained by Kupchan partitioning of 70% methanol extract of leaves of Stevia rebaudiana with n-hexane, dichloromethane and ethyl acetate designated by HSR, DSR and ESR were investigated for their antioxidant and antimicrobial activities. HSR and ESR exhibited prominent free radical scavenging activity having IC50 value of 11.59 and 10.38 μg/ml compared to standard, ascorbic acid (IC50 value 6.05 μg/ml). HSR and ESR also demonstrated significant antibacterial activity by disc diffusion method on some Gram-positive and Gramnegative bacteria. Among the fractions ESR showed the highest antioxidant and antibacterial activity. No significant antifungal activity was observed for any fraction. Preliminary phytochemical screening of all fractions showed the presence of alkaloids, saponin, flavonoids, tannin, carbohydrate and triterpenoids. Total three compounds have been isolated from ESR fraction among which two known compounds (1-2) were characterized as quercitrin (1) and physcion (2) through 1D NMR spectroscopic technique and other one could be a 9,10- anthraquinone derivative which was not characterized yet. The compound physcion (2) is first time report from the plant Stevia rebaudiana. Dhaka Univ. J. Pharm. Sci. 19(2): 191-197, 2020 (December)